Gambaran Organizational Attraction Calon Pelamar Potensial Terhadap Yayasan Y - Karoline Anna Maria; Rayini Dahesihsari (Jurnal Perkotaan, 2018)
Currently there is a trend where young people prefer to work in a start-up than in a large company, even working in nonprofit agencies. But the trend is not perceived by the Yayasan Y, a nonprofit organization of community empowerment through the development of SMEs in Indonesia. The number of applicants for each job advertisements was low. In fact, Yayasan Y will develop the organization in order to expand the scope of SMEs assisted. There were several attempts to increase the number of applicants, such as including the work requirements in more detail and provide salary is quite high compared with other similar foundations and list it on the job ad. But it did not increase the number of applicants significantly. Based on the theory regarding the recruitment of job applicants stated that the decision in choosing a job can be determined by the attractiveness of the organization (Robertson et al, 2005). Organizational attraction is a positive attitude that is owned by an individual on an organization (Aiman-Smith et al, in Catanzaro, Moore, Marshall, and Timothy, 2010). Therefore, researchers wanted to see how the image of the interests of applicants to the Yayasan Y so it can be collated to make strategic measures for the recruitment activities. This study used a mixed method, with quantitative and qualitative approach to describe the interest of young candidates potential applicants to the Yayasan Y as a place to work. Results showed participants actually neutral towards the Yayasan Y as a place to work, but they have never heard of the Yayasan Y before, so they do not have information about the it much. The results also suggest Foundation Y to do branding, through cooperation with other institutions such as the universities in Indonesia.